Facile Solventless Synthesis of a Nylon-6,6/Silver Nanoparticles Composite and Its XPS Study - Raúl A. Morales-Luckie; Víctor Sánchez-Mendieta; Oscar Olea-Mejia; Alfredo R. Vilchis-Nestor; Gustavo López-Téllez; Víctor Varela-Guerrero; L. Huerta; Jesús Arenas-Alatorre (International Journal of Polymer Science)
Silver nanoparticles were synthesized and supported on thin nylon membranes by means of a simple method of impregnation and chemical reduction of Ag ions at ambient conditions. Particles of less than 10 nm were obtained using this methodology, in which the nylon fibers behave as constrained nanoreactors. Pores on nylon fibres along with oxygen and nitrogen from amide moieties in nylon provide effective sites for in situ reduction of silver ions and for the formation and stabilization of Ag nanoparticles. Transmission electron microscopy (TEM) analysis showed that silver nanoparticles are well dispersed throughout the nylon fibers. Furthermore, an interaction between nitrogen of amides moieties of nylon-6,6 and silver nanoparticles has been found by X-ray photoelectron spectroscopy (XPS).